Kaki Diabetes Berulang pada Lansia dengan Non-Adherence Kronik, Diabetes Burnout, dan Risiko Lingkungan Rumah Pesisir Dengan Pendekatan Kedokteran Keluarga : Laporan Kasus - Lely Sustantine Totalia; R. Wianti Soeryani; Novendy Novendy (CV. Jasa Sukses Abadi, 2026)
Recurrent diabetic foot ulcer is a major chronic complication of type 2 diabetes mellitus that contributes to increasedmorbidity, amputation rates, and reduced quality of life, particularly among older adults. Ulcer recurrence is influenced not only by clinical factors but also by medication adherence, psychosocial conditions, family support, and environmentalcircumstances. This case report aims to describe the application of a family medicine approach in managing recurrent diabetic foot ulcer in an elderly patient with multimorbidity and socioeconomic limitations. Mr. S, a 74-year-old man with a five-year history of type 2 diabetes mellitus, hypertension, peripheral neuropathy, and previous foot debridement, presented with a plantar ulcer on the left foot caused by a wooden splinter from the floor of his stilt house. Clinical evaluation revealed a 3 × 2 cm ulcer with moderate infection, HbA1c of 10.2%, poor medication adherence, high diabetes distress, and risk of malnutrition. Holistic assessment identified internal factors including poor glycemic control, chronic non-adherence, and diabetic neuropathy, as well as external factors such as a hazardous coastal home environment, an elderly caregiver, and limited family income. Management was carried out using patient-centered care, family-focused care, and communityoriented care through wound debridement, insulin therapy, antibiotics, intensive diabetic foot care education, medication adherence improvement strategies, home environmental modification, and home visits. Four-week follow-up demonstrated clinical improvement, with ulcer size decreasing to 1.5 × 1 cm, healthy granulation tissue formation, improved medication adherence, and better foot care practices. A comprehensive family medicine approach may improve clinical outcomes and help prevent recurrent diabetic foot ulcers among vulnerable older adults.